Spontaneous magnetostriction constants of aluminium-iron alloys. - Shaari, Abdul Halim
Spontaneous or saturated magnetostriction constants, h1 and h2,for A1-Fe Alloys are presented. It is observed that atomic ordering affects both the constants. The importance of lattice size is also discussed.